Small to Medium-sized Enterprises and Their Financial Report Quality - Astutie, Yanti Puji; Fanani, Baihaqi (International Journal of Economics and Financial Issues, 2016)
This study examined factors affecting the intention to adopt Financial Accounting Standards (FAS) for Small to Medium-sized Enterprises (SMEs) and to use information technology (IT) for financial reporting on SMEs in Central Java Indonesia by using several models. The issue of this research carried from the phenomenon that both things are still a bit carried in Indonesia, to prepare ASEAN economic community. The data obtained from the perception SMEs owners in some cities at Central Java Indonesia, using the survey as primary data. Data analysis was using Partial Least Square to test the correlation and T-test to test the different on the two groups. The results showed that the intention to adopt FAS for SMEs construct could be explained 24% by the variability of the eight other variables with the age of company as a moderating variable. The intention to use information technology (IT) was 57.1%, and implementation construct can be explained by the variability of the intention to adopt FAS SMEs and use IT by 41.6%. This study has limitations on the latent variable constructs and indicators that build construct only several variables. The other limitation is the respondent in question are only on SMEs in Central Java. This study provides the predictive value of the reason why SMEs in Indonesia is lacking in the use of FAS and IT, as well as the intriguing possibilities policy. Keywords: Accounting standards for SMEs, Information Technology, Financial reporting, small to medium-sized enterprises